Ad-DakhÃ„Â«l dalam Tafsir Al-JÃ„Âmi li AhkÃ„Âm Al-QurÃ¢â‚¬â„¢an Karya al-QurtubÃ„Â« - Shofa, Maryam (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
This study will show that some of the narrations cited by al-QurtubÃ„Â« in his commentary of the QurÃ¢â‚¬â„¢an is included in the category of DakhÃ„Â«l al-naql because it includes the sources of problematic narration. The finding comes after the author made an efforts in Takhrij al-hadith in the commentary of the Quran of al-JamiÃ¢â‚¬Ëœ li AhkÃ„Âm al-QurÃ¢â‚¬â„¢Ã„Ân in surah al-Baqarah. Some narrations of the hadith quoted by al-Qurtubi are a fake hadiths, and some others are in form of the passages of Israiliyyat narrations being contradicted to the text of the QurÃ¢â‚¬â„¢an or the common sense as well as the incompetent or fraudulent hadiths which are leaned to the companions of the prophet.Keywords: DakhÃ„Â«l, commentary, al-Qurtubi, the Qur'an .